2018
DOI: 10.1002/srin.201800133
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of Electromagnetic Three‐Phase Flow in a Round Bloom Considering Solidified Shell

Abstract: A large eddy simulation (LES) model has been developed to simulate three‐phase flow, heat transfer, and solidification processes under the effect of M‐EMS. Through comparing the magnetic flux density, surface temperature, and growth of solidified shell with experimental results, the reliability of our mathematical model is proved. Results show that the ignorance of solidified shell will overestimate the velocity field and slag‐metal interface fluctuation, therefore the solidified shell should not be ignored. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The transient external magnetic field was generated from the alternating current. The magnetic flux density and the current distribution were solved in a transient solver [39,40]. The following three equations were computed in the solver:…”
Section: Electromagnetic Stirring Forcementioning
confidence: 99%
“…The transient external magnetic field was generated from the alternating current. The magnetic flux density and the current distribution were solved in a transient solver [39,40]. The following three equations were computed in the solver:…”
Section: Electromagnetic Stirring Forcementioning
confidence: 99%
“…Here, the term ρ m is mixture density, P is the static pressure, F is the particle force acted on steel, F T is the surface tension at the interface [21], and the µ e f f ect = µ m + µ t is the effective viscosity of mixture phase. The term µ m is the molecular viscosity of the mixture phase and µ t is the turbulent viscosity of mixture phase.…”
Section: Les Modelmentioning
confidence: 99%
“…Many researchers have investigated the fluctuations of the slag-metal interface in the mold [17,20,21]. However, the interface fluctuations are monitored only on some limited points.…”
Section: Turbulent Behavior Of Two Interfaces In the Moldmentioning
confidence: 99%
“…The flow pattern in the lower recirculation zone is asymmetrical and changes over a certain period; however, the periodical flow in these studies was found in slabs with a two-port submerged entry nozzle (SEN). Until now, there have been few reports about asymmetrical flows injected from a straight nozzle, except for some works by Willers [22] and Li [23]. Based on the experiment of Willers [22], there exists a secondary motion in the upper part of the mold, and this causes a strong deformation of the free surface during and after MEMS.…”
Section: Introductionmentioning
confidence: 99%